2021
DOI: 10.1001/jamanetworkopen.2021.8787
|View full text |Cite|
|
Sign up to set email alerts
|

Cost-effectiveness of Nivolumab-Ipilimumab Combination Therapy for the Treatment of Advanced Non–Small Cell Lung Cancer

Abstract: Key Points Question Is nivolumab-ipilimumab combination therapy cost-effective as first-line treatment for patients with advanced non–small cell lung cancer compared with platinum-doublet chemotherapy? Findings In this economic evaluation of the cost-effectiveness of nivolumab-ipilimumab combination therapy, a Markov model was designed to simulate patients with advanced non–small cell lung cancer who were receiving either nivolumab-ipilimumab combination th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…This finding could be attributed to a lower survival benefit of N+I versus chemotherapy in PD-L1 ≥ 1% subgroup than that in PD-L1 < 1% subgroup ( 6 ). Similar ICER results were also recognized in two previous studies ( 17 , 18 ). Although exploratory analysis of the trial showed that N+I provided preferable survival benefits in patients with PD-L1 ≥ 50% or high tumor mutational burden, we did not perform these subgroup analyses because of the absence of valid data.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding could be attributed to a lower survival benefit of N+I versus chemotherapy in PD-L1 ≥ 1% subgroup than that in PD-L1 < 1% subgroup ( 6 ). Similar ICER results were also recognized in two previous studies ( 17 , 18 ). Although exploratory analysis of the trial showed that N+I provided preferable survival benefits in patients with PD-L1 ≥ 50% or high tumor mutational burden, we did not perform these subgroup analyses because of the absence of valid data.…”
Section: Discussionsupporting
confidence: 91%
“…Although several investigations have shown a single-agent ICI with or without chemotherapy to be cost-effective (11)(12)(13)(14)(15), doubleagent ICI combinations incur more costs than single-ICI regimens. To date, three studies have estimated the cost-effectiveness of N+I versus chemotherapy and displayed different results (16)(17)(18). Another recently published study found that the incremental costeffectiveness ratio (ICER) of N+I+chemotherapy versus chemotherapy alone was $202,275 per quality-adjusted life year (QALY) (19).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the utility values and treatment costs for AEs in our model were obtained from other published literature. 23 , 24 , 26 We assumed that AEs occurred only in the first cycle. Precise utility scores were not available in the original or previous MPM literature.…”
Section: Methodsmentioning
confidence: 99%
“…The potential reason is that maintenance chemotherapy is considered in nonsquamous tumors, which substantially augments the cost of chemotherapy in nonsquamous tumors compared with squamous tumors. The recent two economic analyses showed the opposite results (Hu et al, 2020;Courtney et al, 2021), which might be led by the different gained health outcomes. However, nivolumab plus ipilimumab is not a cost-effective option in the Chinese context because its ICER exceeded the local threshold of $27,351/QALY.…”
Section: Discussionmentioning
confidence: 97%